THEMATIC ANALYSIS OF HADITH TEXTS ON ABLUTION AND THAHARAH FROM THE PERSPECTIVE OF HUMAN BODY BIOLOGY - Laila Kamilatul Rahmi; Lailan Najmi; Inong Satriadi (Journal International Inspire Education Technology, 2025)
The hadith texts on ablution and taharah have been understood predominantly within the framework of normative fiqh, while the biological dimension of the human body as an object of purification practice is relatively rarely analyzed systematically. In fact, the practice of ablution touches on body organs that have certain physiological and biological functions. This study primarily aims to analyze the meaning of thaharah in the hadith on ablution and its relevance to the principles of human biological hygiene through a thematic qualitative approach. This objective has a methodological urgency that aligns with the direction of contemporary Islamic education policy that encourages the integration of knowledge (ta'dib) between revelation and empirical science. This study uses a qualitative approach, which is ideal for understanding phenomena in depth based on the context and meaning contained in the text. The results of this study indicate that thaharah cannot be separated from three structured principles of biological hygiene: microbiological, physiological, and neurological. This study concludes that the meaning of thaharah in the hadith on ablution has a very strong and structured relevance to the principles of human biological hygiene. Through thematic analysis, three main themes were identified: self-purification as spiritual-physiological maintenance, ablution as a mechanism for bodily homeostasis, and hygiene as an integrated physical-spiritual system.